ANALISIS WAKTU TUNGGU PELAYANAN RESEP PASIEN JKN RAWAT JALAN DI UNIT FARMASI RS PROF. DR. TABRANI PEKANBARU TAHUN 2018 - Faulin, Dovy Saptika; Hartono, Budi; Wahyudi, Arief (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
One important indicator of maintaining hospital quality performance is the waiting time for prescription services. The last 6 months data, 60.9% recipe non-concoction and 52.8% recipe concoction exceeds the minimum standard based on the Decree of the Ministry of Health RI No.129/Menkes/SK/II/2008 for prescription concoction menit 60 minutes and noncream â‰¤ 30 minutes. The purpose of the study was to find out the point of waiting time for outpatient JKN prescribing services and the influencing factors. Qualitative research methods through informants based on the principles of appropriatness and adequacy. For the problem point taken 110 recipe sheets. The results of the study average non-concoction prescription 83.76 minutes and concoction 91.08 minutes. The conclusions of the longest point of time before the non-drug drug retrieval process and before the preparation process of concoction drugs, are influenced by inadequate human resources and incompatibility, lack of skills knowledge, education and training have not been carried out, narrow preparation space, SIMRS has not been integrated, availability of drugs is lacking, funding allocation from BPJS Health claims, procedures are unclear, patient participation is lacking, prescribing outside the formulary and doctor's practice is not timely.